Clinical significance and heterogeneity of circulating tumor cells and clusters in breast cancer subtypes - LiangYu Hao; Lixiang Zheng (PeerJ, 2025)
The marked heterogeneity of breast cancer results in substantial variations in clinical characteristics, metastatic patterns, and prognosis across molecular subtypes. However, circulating tumor cells (CTCs) and circulating tumor cell clusters (CTC clusters), pivotal mediators of metastasis, have not been comprehensively evaluated for their biological characteristics and clinical significance across molecular subtypes. This review synthesizes recent research advancements to comprehensively examine the distribution characteristics, biological functions, and prognostic associations of CTCs and CTC clusters in luminal A, luminal B, HER2-positive breast cancer, and triple-negative breast cancer (TNBC). It was observed that HER2-positive breast cancer is associated with elevated CTC counts, whereas TNBC, despite lower CTC counts, exhibits CTCs and CTC clusters with enhanced invasiveness and metastatic potential due to Notch1 signaling pathway activation, elevated PD-L1 expression, and desialylation modifications. In luminal subtypes, the scarcity of CTC clusters is linked to a reduced metastatic risk; however, luminal B exhibits a greater propensity for CTC cluster formation than luminal A, suggesting prognostic differences. Clinical data demonstrate that CTC cluster counts are significantly inversely correlated with overall survival (OS) and disease-free survival (DFS), and that dynamic monitoring of CTC clusters enables prediction of treatment resistance and recurrence risk. Furthermore, the molecular profiles of CTCs (e.g., HER2 status, ESR1 mutations) facilitate personalized guidance for targeted and endocrine therapies. However, current detection technologies exhibit limitations in capturing CTC clusters with high efficiency and sensitivity, necessitating further optimization through microfluidic sorting, single-cell omics, and artificial intelligence approaches. This review underscores the heterogeneity of CTCs and CTC clusters across breast cancer subtypes, alongside their potential for clinical translation, offering theoretical support for prognostic evaluation and individualized treatment strategies in precision medicine. This study may be of considerable value to researchers and clinicians in the field of cancer metastasis.